2015
DOI: 10.1111/1750-3841.13138
|View full text |Cite
|
Sign up to set email alerts
|

Foodborne Pathogens Prevention and Sensory Attributes Enhancement in Processed Cheese via Flavoring with Plant Extracts

Abstract: Cheese contaminations with foodborne bacterial pathogens, and their health outbreaks, are serious worldwide problems that could happen from diverse sources during cheese production or storage. Plants, and their derivatives, were always regarded as the potential natural and safe antimicrobial alternatives for food preservation and improvement. The extracts from many plants, which are commonly used as spices and flavoring agents, were evaluated as antibacterial agents against serious foodborne pathogens, for exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 45 publications
(59 reference statements)
1
29
0
Order By: Relevance
“…Divergent results have been reported in several studies, including those of Leuschner and Ielsch (2003), Hayaloglu and Fox (2008), Gammariello et al (2008), who all affirmed that TEO has been successfully incorporated into cheese and have been well accepted by consumers. Tayel et al (2015) also confirmed that addition of TEO to cheeses resulted in good sensory acceptance. Gouvea et al (2017) mentioned that general acceptance of cheeses with essential oils and plant extracts can be facilitated if consumers are already familiar with this type of products.…”
Section: Evaluation Of Sensory Cheese Qualitysupporting
confidence: 62%
“…Divergent results have been reported in several studies, including those of Leuschner and Ielsch (2003), Hayaloglu and Fox (2008), Gammariello et al (2008), who all affirmed that TEO has been successfully incorporated into cheese and have been well accepted by consumers. Tayel et al (2015) also confirmed that addition of TEO to cheeses resulted in good sensory acceptance. Gouvea et al (2017) mentioned that general acceptance of cheeses with essential oils and plant extracts can be facilitated if consumers are already familiar with this type of products.…”
Section: Evaluation Of Sensory Cheese Qualitysupporting
confidence: 62%
“…The overall prevalence of 4% was regarded as lower compared to data reported in 1999, but the isolates showed resistance to up to seven antimicrobials [56]. A significant higher prevalence with 41% (65/158) of samples found positive for Salmonella was reported in case of dog treats derived from pig ears and other animal parts randomly collected in USA [28].…”
Section: Multidrug Resistance In Animalsmentioning
confidence: 71%
“…Literature gathers a multitude of scientific studies that support the use of whole plant extracts in therapeutics, and the vast majority of researchers indicate medicinal plants as a viable alternative for the antimicrobials [13,24,[26][27][28][29].…”
Section: Antimicrobial Resistance -A Global Threatmentioning
confidence: 99%
See 1 more Smart Citation
“…Listeria is killed by pasteurization, and outbreaks of this bacterial strain have rarely been associated with pasteurized dairy products, including cheese (Koch et al, 2010). These foodborne bacteria are of concern for the dairy industry because they have been identified in different dairy products and have been implicated in outbreaks (Kousta et al, 2010;Yang et al, 2012;Claeys et al, 2013;Ricci et al, 2013;Robinson et al, 2014;Tayel et al, 2015;Pouillot et al, 2016).…”
Section: Bacteria Involved In Dairy Product Contaminationmentioning
confidence: 99%